Motivation of Employees 50+ - Danica Bakotić; Srećko Goić; Ivana Tadić (European Scientific Journal, ESJ, 2018)
In recent years, employees older than 50 years of age represent a significant work force and companies have become aware of their importance. They have to be managed in a specific way by motivating and encouraging them in achieving extraordinary performance. However, in the literature, there is a lack of empirical research about older employees. Because of that, the aim of this paper is to explore the motivation of employees 50+ This paper is based on the large empirical investigation conducted within the project InCounceling 50+ co-funded by the European Commission through the Erasmus+ Programme. The research in Croatia was conducted in 2017 in 6 Croatian companies. The research instrument was a specially designed questionnaire with 30 questions. The questions relevant for this paper were about employees’ general characteristics, employees’ competencies and motivational factors. These questions were completed by 141 employees. The collected data was analyzed by the usual statistics methods supported by SPSS program. The research results showed that employees 50+ consider that they have sufficient or even higher competencies required for their job position. Regarding motivational factors, good atmosphere at work is the most important motivational factor for employees 50+, followed by the respect and recognition and safety and stability of the employment. Career development is the least important motivational factor for employees 50+. Additionally, research results showed that there are no statistically significant differences in motivational factors of employees 50+ regarding their gender, educational level and job position.